Akuntabilitas Pengelolaan Keuangan Desa Adat (Studi pada Desa Adat Buleleng, Kecamatan Buleleng, Kabupaten Buleleng) - Putu Erwin Satya Arya Pramana; Ni wayan Yulianita Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study aims to gain an understanding of the practice of financial management in Buleleng Traditional Village, Buleleng District, Buleleng Regency. The phenomenon that occurs in the Traditional Village of Buleleng is that the traditional village of Buleleng has been in office for more than two periods and there have been no cases of fraud in the financial management of the Traditional Village of Buleleng. In this study using a qualitative descriptive method. Data collection is done by observation, interview and documentation. Meanwhile, data analysis uses the Miles and Huberman model which consists of data reduction, data presentation, data analysis and conclusion drawing. The results of this study stated that Buleleng Adat Village carried out financial management related to the allocation of adat village funds from the provincial government focusing on 3 (three) processes, namely planning, implementation and accountability. Accountability in the process of accountability for the management of customary village funds in the Traditional Village of Buleleng always documents every activity carried out and also makes a financial report on the use of the allocation of customary village funds from the provincial government in accordance with the technical instructions in the Governor of Bali Regulation No. 34 of 2019 concerning Management of Indigenous Village Finance. This financial report is a form of accountability that is submitted to the manners (community) during paruman (meeting) on Friday the first week of each month at the grand hall of Pura Desa Desa Desa Adat Buleleng.